(untitled) (European Journal of Interdisciplinary Studies, 2017)
Knowledge Management is an important and significant segment of the Management discipline. Military units and formations could use this valuable asset in their operations. Unfortunately, the academic world could hardly address the knowledge management issues, particularly the knowledge transfers mechanisms in the military context. This paper makes an endeavour to fill up this gray area of the academic world. The exhibited knowledge transfer mechanisms show how military forces use various techniques and mechanisms to transfer knowledge between the knowledge contributors and recipients. The paper will help the business organisations borrow the military knowledge transfer mechanisms. The transfer mechanisms used in military forces presented here provide a deeper understanding of characteristics and nature of the mechanisms; Some of them are different and unique from those of the corporate/business world. Future researchers may empirically examine these mechanisms in military context.